MANAGEMENT IN THE SYSTEM OF PROFESSIONAL RETRAINING OF PEDAGOGICAL STAFF - H.B. Shtelmakh (Academy of Cognitive and Natural Sciences, 2004)
This article concerns the abilities of pedagogical management during the process of pedagogical training as one of the ways of professional readiness.